(untitled) (Asian Journal of Pharmaceutics (AJP), 2021)
Introduction: Clomiphene citrate is a nonsteroidal ovulation inducer used in the treatment of infertility. This drug belongs to biopharmaceutical classification system Class-II often possesses challenges concerning solubility or poor dissolution, drug release, and thereby enhance the bioavailability. Aim: The aim of the study was to improve the solubility of the drug as well as to make the formulation more feasible liquisolid technique was adopted. Materials and Methods: Here, Avicel PH 102(Q) and Aerosil 200(q) in varying ratios ranging from 5, 10, 20, and 25 were employed as coating and carrier materials (R=Q/q), and their quantities incorporated into formulation were calculated based on the mathematical formulae developed by Spireas and final powder substrate developed was compressed into a tablet by direct compression method. Twelve formulations LS1 to LS12 were prepared and subjected to drug excipient interactions studies, pre-compression, and post-compression studies and compared with the marketed formulation. Results and Discussion: The Fourier transform infrared spectroscopy results showed no interaction between drug-excipients. Scanning electron microscopy and X-ray diffractometry analysis indicated that the clomiphene citrate is held within the powder substrate in a solubilized, almost molecularly dispersed state and in liquisolid as an amorphous powder with no signs of instability on storage. An optimized formulation was selected based on the in vitro, drug release studies. LS2 formulation containing Avicel PH 102(Q):Aerosil 200(q) a ratio of 10:1 and drug concentration 10% exhibited the controlled and complete/highest drug release rate of 96.46% in 30 min in comparison with the marketed product. Conclusion: Thus, we propose that liquisolid technique can be chosen as the most economical and alternative approach to enhance the solubility of clomiphene citrate.